Total factor productivity and technical efficiency differences of aquaculture farmers in Bangladesh: Do environmental characteristics matter? - Sandip Mitra; Md Akhtaruzzaman Khan; Rasmus Nielsen; Nazrul Islam (Wiley, 2025)
This study examines how production environment characteristics affect total factor productivity (TFP) and technical efficiency (TE) in aquaculture farms. Enhancing productivity is important for increasing resource use efficiency, especially in developing countries where improvements in the aquaculture sector can enhance food security for low- and middle-income people and improve farmer livelihood. In the present study, 580 aquaculture farms from different areas of Bangladesh were sampled using stratified random sampling techniques. A Fisher quantity index and data envelopment analysis were used to analyze TFP and TE, respectively. In addition, a rank-sum test was used to investigate how production environment characteristics affect TFP and TE. The results show that farmers could significantly reduce input while maintaining the same level of output. Furthermore, they demonstrate that the TFP and TE of a farm are significantly affected by environmental characteristics, varying with geographical variation in water availability, color, and plants; feed types; and culture systems.Dissemination of the results through training programs and extension services provided by public or private stakeholders could help extensive pond farmers in developing countries improve productivity and efficiency and thereby help provide food and improve livelihood conditions in developing countries.